Accountability in Decentralised Employment Service Regimes - Mosley, Hugh (OECD Local Economic and Employment Development (LEED) Papers, 2012)
The Accountability in Decentralised Employment Service Regimes report, prepared by independent expert Hugh Mosely, compares and contrasts four OECD countries with decentralised delivery systems for managing active labour market policy (Canada, Belgium, the Netherlands and Denmark). This report contextualises the findings of the OECD LEED "Managing Accountability and Flexibility" study in current academic discussions relating to new performance management and accountability